Depression in Parents, Parenting, and Children: Opportunities to Improve Identification, Treatment, and Prevention - Medicine, Institute of; Council, National Research; Education, Division of Behavioral and Social Sciences and; Board on Children, Youth, and Families; Committee on Depression, Parenting Practices, and the Healthy Development of Children (National Academies Press, 2009)
Depression is a widespread condition affecting approximately 7.5 million parents in the U.S. each year and may be putting at least 15 million children at risk for adverse health outcomes. Based on evidentiary studies, major depression in either parent can interfere with parenting quality and increase the risk of children developing mental, behavioral and social problems. Depression in Parents, Parenting, and Children highlights disparities in the prevalence, identification, treatment, and prevention of parental depression among different sociodemographic populations. It also outlines strategies for effective intervention and identifies the need for a more interdisciplinary approach that takes biological, psychological, behavioral, interpersonal, and social contexts into consideration. A major challenge to the effective management of parental depression is developing a treatment and prevention strategy that can be introduced within a two-generation framework, conducive for parents and their children. Thus far, both the federal and state response to the problem has been fragmented, poorly funded, and lacking proper oversight. This study examines options for widespread implementation of best practices as well as strategies that can be effective in diverse service settings for diverse populations of children and their families. The delivery of adequate screening and successful detection and treatment of a depressive illness and prevention of its effects on parenting and the health of children is a formidable challenge to modern health care systems. This study offers seven solid recommendations designed to increase awareness about and remove barriers to care for both the depressed adult and prevention of effects in the child. The report will be of particular interest to federal health officers, mental and behavioral health providers in diverse parts of health care delivery systems, health policy staff, state legislators, and the general public.